Determination of bacterial microbiological quality in Oreochromis niloticus and Coptodon rendalli tissue from Porce II and Porce III reservoirs, Antioquia - Colombia - Luisa Londoño-Ramírez; Carolina Zapata-Escobar; Luz Orozco-Jiménez; Jaime Palacio-Baena (Actualidades Biológicas, 2022)
The Porce II and Porce III reservoirs are located northeastern of the department of Antioquia, have poor water quality due to the entry of chemical and biological contaminants from domestic and industrial wastewater discharge from ten municipalities that are part of the Aburrá Valley. Artisanal fisheries have been reported in the reservoirs with low safety standards for self-consumption and commercialization. Food safety is fundamental for the assurance of public health. Colombian regulations for the consumption of fishery products focus on risk prevention and warn of improper handling and/or contamination of the fishery product (NTC1443:2016 and Resolution:776/2008, modified by Resolution:122/2012). This project sought to determine the bacterial microbiological quality of Oreochromis niloticus and Coptodon rendalli muscle from Porce II and Porce III reservoirs by analyzing the indicators total coliforms, thermo-tolerant Escherichia coli, Staphylococcus aureus and Salmonella spp. in eight samplings between March 2018 and October 2019, 480 specimens were purchased from local fishermen. Total length, standard length, and weight of each fish was determined, and microbiological indicators were analyzed following Colombian standards (NTC4458, NTC4779, NTC4574). Under these criteria, more than 80% of the samples showed non-compliance because they exceeded the permitted limits for microbial load. The health risk for human and wild communities that feed on these contaminated fish is inferred.